Report of the Monitoring and Evaluation Workshop - Atengdem, Paschal (CGIAR Challenge Program on Water and Food, 2011)
The Monitoring and Evaluation workshop was organized for key staff of the Volta Basin Development Challenge (VBDC) as part of the process in developing a Monitoring Plan for the VBDC of the Challenge Programme Water and Food (CPWF) Phase II. The Challenge Programme on Water & Food in Volta Basin (CPWF-Volta) was initiated as part of the global CGIAR Challenge program on Water and Food currently on-going in Asia, Africa and South America. The CPWF research (Phase II) in the basin is planned to run from 2010 -2013 as a follow-up on the first Phase of CPWF which ran from 2003-2009. The current program explores the institutional and technical aspects of small reservoir development and maintenance, embedded within a wider rainwater management system for the Volta River Basin.